Geo-climatic potential of direct evaporative cooling in the Mediterranean Region: A comparison of key performance indicators. (15th March 2019) - Chiesa, Giacomo; Huberman, Nora; Pearlmutter, David
Abstract: This study analyses the geo-climatic applicability of passive direct evaporative cooling (DEC) for improving indoor thermal comfort in the Mediterranean Region. An initial climate-dependent evaluation of the potential for implementing DEC in selected reference locations was performed using three different methodologies, including a comparison of two new key performance indicators with an existing method. The potential of DEC is then evaluated in detail by conducting thermal simulations for a prototype office building in 60 cities representing different Mediterranean climate zones, and by comparing different building configurations to analyse the influence of various design parameters on the potential for effective space cooling. Results show that the potential for increasing comfort through DEC is highly dependent on key parameters that impact the need for cooling, such as controlled natural ventilation, internal heat gains and thermal insulation. Finally, results from the initial evaluations are compared with those from the detailed building simulation to quantify the correlation between the two approaches, and to gauge the usefulness of climate-based analyses for the early evaluation of DEC applicability in a given location. The new methods for assessing the geo-climatic applicability of DEC (on an hourly basis) are shown to be feasible when compared to dynamic simulations, indicated by a significant correlation between the two. These new approaches therefore offer evaluation methods for designers considering DEC technologies during the early phases of building design. Furthermore, considering application in the study, DEC is shown to be an effective technique for low-energy cooling, especially in the Eastern Mediterranean and southern Spain. Highlights: We assess the potential of direct evaporative cooling for office design. New methods are introduced for practical assessment of DEC potential. Dynamic energy simulations allow comparison between indicators. Sensitivity analysis is made on the impact of envelope characteristics. Comfort analysis is based on temperature and relative humidity.